SEJARAH PONDOK PESANTREN NURUL JALAL DI KECAMATAN TEBO TENGAH KABUPATEN TEBO - Hendra Gunawan (Jurusan Sejarah Peradaban Islam Fakultas Adab dan Humaniora UIN Sulthan Thaha Saifuddin Jambi, 2020)
Pondok Pesantren Nurul Jalal is constantly experiencing dynamics and struggling with social reality that does not stop changing. The dynamics in the form of a struggle between ideas, values, and traditions that are considered noble with the challenges of life and social change that is always rolling and all that must be passed by the Ponpes Nurul Jalal. To see the history of the development of the Ponpes Nurul Jalal, the method used is a historical research method, with a heuristic process; source criticism; interpretation and historiography. Furthermore, the findings in this study explain in 1994 stood Ponpes Nurul Jalal in Central Tebo District by KH Muhammad Manshur. The name of the Ponpes Nurul Jalal was taken from the name of the Ponpes Nurul Jalal in Mangun Jayo Village. The development of Ponpes Nurul Jalal originated from the leadership of KH. Muhammad Manshur who is a charismatic leader. After that, the leadership was continued by H. M. Fauzi Manshur who was more on collective leadership. Changes in leadership patterns certainly affect the development of teachers, students and curriculum in Ponpes Nurul Jalal.